Bundling Demand in K-12 Broadband Procurement - Gaurab Aryal; Charles Murry; Pallavi Pal; Arnab Palit (Center for Economic Studies and ifo Institute (CESifo), 2024)
We evaluate the effects of bundling demand for broadband internet by K-12 schools. In 2014, New Jersey switched from decentralized procurements to a new procurement system that bundled schools into four regional groups. Using an event study approach, we find that, on average, prices for participants decreased by one-third, and broadband speed purchased increased sixfold. We bound the change in school expenditures due to the program and find that participants saved at least as much as their total "E-rate" subsidy from the federal government. Under weak assumptions on demand, we show that participating schools experienced large welfare gains.
Keywords: D44; H42; L86; L96; 330; broadband internet; exposure problem; bundling; welfare